Effect Of Rational Emotive Behaviour Therapy (Rebt) With Endurance Training In Irrational Belief And Precompetitive Anxiety On Pistol Shooters (Journal of Pharmaceutical Negative Results, 2023)
Shooters require comprehensive training including physical, mental and technical components for overall successful performance. There is a dearth of existing literature on multidisciplinary training. The aim of the present study is to find out the effect of Rational Emotive Behaviour Therapy along with strength training on elite level pistol shooters. The present study was a randomized controlled trial with 60 participants who were elite shooters from various shooting ranges of Punjab. Participants were divided into two groups (I and II) according to a computerized randomization table. The Experimental Group I underwent REBT training twice a week, Physical training thrice a week for 2 months and other group II followed strength and endurance training. The short general attitude belief scale (SGABS), and SCAT , Salivary cortisol collected on pre training (0 day) and post training (60th , 90th day) from participants of both groups. The data were analyzed with repeated measure one way ANOVA using SPSS version 20. The result shows that experimental group I has statistically significant reduction in SGABS score (p < 0.00), SCAT score (p < 0.00), Salivary cortisol (p < 0.00) relative to that of group II. The present study revealed that comprehensive training is more beneficial for reducing precompetitive anxiety pistol shooters.